SGLT2 Inhibition, Choline Metabolites, and Cardiometabolic Diseases: A Mediation Mendelian Randomization Study - Xu, Min; Zheng, Jie; Hou, Tianzhichao; Lin, Hong; Wang, Tiange; Wang, Shuangyuan; Lu, Jieli; Zhao, Zhiyun; Li, Mian; Xu, Yu; Ning, Guang; Bi, Yufang; et al. (Diabetes care, 2022)
To investigate the causal role of choline metabolites mediating sodium-glucose cotransporter 2 (SGLT2) inhibition in coronary artery disease (CAD) and type 2 diabetes (T2D) using Mendelian randomization (MR). A two-sample two-step MR was used to determine 1) causal effects of SGLT2 inhibition on CAD and T2D; 2) causal effects of three choline metabolites, total choline, phosphatidylcholine, and glycine, on CAD and T2D; and 3) mediation effects of these metabolites. Genetic proxies for SGLT2 inhibition were identified as variants in the SLC5A2 gene that were associated with both levels of gene expression and hemoglobin A1c. Summary statistics for metabolites were from UK Biobank, CAD from CARDIoGRAMplusC4D (Coronary ARtery DIsease Genome wide Replication and Meta-analysis [CARDIoGRAM] plus The Coronary Artery Disease [C4D] Genetics) consortium, and T2D from DIAbetes Genetics Replication And Meta-analysis (DIAGRAM) and the FinnGen study. SGLT2 inhibition (per 1 SD, 6.75 mmol/mol [1.09%] lowering of HbA1c) was associated with lower risk of T2D and CAD (odds ratio [OR] 0.25 [95% CI 0.12, 0.54], and 0.51 [0.28, 0.94], respectively) and positively with total choline (β 0.39 [95% CI 0.06, 0.72]), phosphatidylcholine (0.40 [0.13, 0.67]), and glycine (0.34 [0.05, 0.63]). Total choline (OR 0.78 [95% CI 0.68, 0.89]) and phosphatidylcholine (OR 0.81 [0.72, 0.91]) were associated with T2D but not with CAD, while glycine was associated with CAD (0.94 [0.91, 0.98]) but not with T2D. Mediation analysis showed evidence of indirect effect of SGLT2 inhibition on T2D through total choline (0.91 [0.83, 0.99]) and phosphatidylcholine (0.93 [0.87, 0.99]) with a mediated proportion of 8% and 5% of the total effect, respectively, and on CAD through glycine (0.98 [0.96, 1.00]) with a mediated proportion of 2%. The results were well validated in at least one independent data set. Our study identified the causal roles of SGLT2 inhibition in choline metabolites. SGLT2 inhibition may influence T2D and CAD through different choline metabolites.